The United States of America and The Fight Against Corruption in Nigeria, 2015-2020: A Critical Analysis - Opakunbi, Oyedamade Tope; Babajide, Jacob (NIU Journal of Humanities, 2022)
Corruption as a major blight of most developing states around the world is an endemic that has systematically eaten deep into the core of Nigeria as a system. Considering selected approaches to tackle corruption in Nigeria since 1999, the expository design was adopted to appraise the efforts of the United States (US) in the anti-corruption operations in Nigeria. The study confirmed that Nigeria has the highest stake in its anti-corruption struggles. It concluded that Nigeria and the US can work together against corruption in Nigeria. However, Nigeria’s expectations of the US in this regard should be moderate, in recognition of the latter’s interest. Although the US has projected interest in the anti-corruption fight in Nigeria in many high-profile discussions, the study recommended that the US should begin to make its efforts believable by dissociating itself from corrupt Nigerian elites. In furtherance of its anti-corruption drive, the US should also be confrontational through rigorous questioning of funds laundered to be spent or invested in the US. Keywords: Corruption, Anti-corruption, Nigeria, United States (US), Developing States